It's our time! Cross Country Canada`s Strategic Plan to 2018(+) (Cross Country Canada, 2013)
This material presents the mission, mandate and vision of Cross Country Canada as well as the strategic planning for the next years - the long-term goals up to 2018(+), the Corporate Strategy - "It`s Our Time!" and mid-term objectives for 2014. Annex A shows as a strategic assessment CCC`s situation in 2009/10.